They Met at Wounded Knee : The Eastmans' Story - Eick, Gretchen Cassel, 1942- (Book collections on Project MUSE., 2020)
"They Met at Wounded Knee is a historical biography of Sioux physician Charles Ohiyesa Eastman and his Euro-American wife Elaine Goodale who first met at Pine Ridge Reservation a month before the Wounded Knee Massacre. The book draws on their numerous books, speeches, Congressional lobbying, and organization of Indian communities to tell the story of the plight of America's Indigenous People from 1890 to 1940 and to expose the corruption and mismanagement of U.S. Indian policy"--